1985
DOI: 10.1038/316148a0
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin reverses adenosine inhibition of neuronal glutamate release

Abstract: Adenosine and its analogues are potent inhibitors of synaptic activity in the central and peripheral nervous system. In the central nervous system (CNS), this appears to arise primarily by inhibition of presynaptic release of transmitters, including glutamate, which is possibly the major excitatory transmitter in the brain. In addition, postsynaptic effects of adenosine have been reported which would also serve to reduce neurotransmission. The mechanism by which adenosine inhibits CNS neurotransmission is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(81 citation statements)
references
References 22 publications
6
74
1
Order By: Relevance
“…Although the exact anatomical sites and molecular mechanisms involved in the mediation of adenosine receptors effects in ethanol hangover are not known, a speculative hypothesis can be given. Previous studies have demonstrated that adenosine A 1 receptor agonists can inhibit the neural release of glutamate (Dolphin and Prestwich, 1985;Fredholm et al, 1989) and acetylcholine (Jin et al, 1993;Ribeiro et al, 1996), two excitatory neurotransmitters that have been implicated as playing an important role in the ethanol withdrawal syndrome (Rossetti and Carboni, 1995;Imperato et al, 1998). Thus, this mechanism may underlie the present effectiveness of adenosine and CCPA in reducing acute ethanol withdrawalinduced anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…Although the exact anatomical sites and molecular mechanisms involved in the mediation of adenosine receptors effects in ethanol hangover are not known, a speculative hypothesis can be given. Previous studies have demonstrated that adenosine A 1 receptor agonists can inhibit the neural release of glutamate (Dolphin and Prestwich, 1985;Fredholm et al, 1989) and acetylcholine (Jin et al, 1993;Ribeiro et al, 1996), two excitatory neurotransmitters that have been implicated as playing an important role in the ethanol withdrawal syndrome (Rossetti and Carboni, 1995;Imperato et al, 1998). Thus, this mechanism may underlie the present effectiveness of adenosine and CCPA in reducing acute ethanol withdrawalinduced anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…Presynaptically, adenosine inhibits synaptic transmission by decreasing the amount of transmitter released (Kocsis et al, 1984;Malenka and Kocsis, 1988;Prince and Stevens, 1992;Scanziani et al, 1992;Scholz and Miller, 1992). Direct measurements of glutamate release have confirmed that adenosine can diminish stimulation-evoked release of glutamate from brain slice and from cultured neurons (Dolphin and Archer, 1983;Corradetti et al, 1984;Dolphin and Prestwich, 1985). Postsynaptically, adenosine hyperpolarizes cells by increasing a postsynaptic K+ conductance (Greene and Haas, 1985;Trussell and Jackson, 1985;Proctor and Dunwiddie, 1987;Gerber et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Dolphin & Prestwich (1985) postulated the involvement of N, in the A,-receptor-mediated inhibition of glutamate release from the finding that IAP prevented the (-)-N6-(Rphenylisopropyl adenosine ((-)-PIA)-induced inhibition of adenylate cyclase and altered the inhibition of release to facilitation. Evidence for the involvement of a regulatory N-protein in the autoinhibitory feedback mechanism of noradrenergic nerve terminals of the rabbit hippocampus has been shown by the finding that both IAP as well as NEM diminished the autoreceptor-mediated effects on noradrenaline release (Allgaier et al, 1985;1986).…”
Section: Introductionmentioning
confidence: 99%